Pengaruh Modifikasi Pembelajaran Permainan Invasi Bola Tangan Menerapkan Media Bola Karet Terhadap Hasil Belajar Kelas V SDN Lidah Wetan II/462 Surabaya - Dinda Anggi Winarta; Faridha Nurhayati; Indra Bagus Lesmana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Volleyball was still employed in the learning materials at the time of the handball material. Students became less engaged in their PJOK studies as a result, particularly with the content related to the handball invasion game. The aim of this study was to enhance the learning outcomes of 26 students in class V-A at SDN Lidah Wetan II Surabaya using classroom action research. The experimental research method was the research strategy employed in this investigation. The significant value of the pretest and posttest is 0.000, or less than 0.05, as can be seen from the paired simple t test results in the above table. The homogeneity and normality test indicates that the data is homogeneous and normally distributed. The paired simple t test on social skills yields a significant influence from the student's social skills test results, with a significance value of less than 0.05. The study's findings suggest that, in addition to producing a fun learning environment, handball invasion learning with rubber ball media can enhance student learning outcomes, focus and activity levels, and social skills development. In the end, learning results for students can be raised.